PELABELAN E-CORDIAL PADA BEBERAPA GRAF CERMIN - Ermi Suwarni; Lucia Ratnasari (Jurnal Matematika, 2012)
Abstract: Let G be a graph with vertex set V(G) and edge set E(G) . Difine on function f of E(G) to {0,1}, for v∈V(G) value f(v) is obtained by two modulo price of amount of edges label than have insident to the vertex v . The function f is called an E -cordial labeling of G if conditions absolute value from difference the number of vertexs having label 0 and the number having label 1 less or equal 1, and absolute value from difference the number of edges having label 0 and the number of edges having label 1 less or equal 1. Graph which admits of E -cordial labeling is E-cordial graph. The mirror graph M(G) is a bipartite graph with a partite sets V1 and V2 and G' be the copy of G with corresponding partite sets V'1 and V'2 . The mirror graph is obtained by joining each vertex of vi∈V2 to its corresponding vertex in v'i∈V2' by an edge. In this paper we study about labeling of mirror graph for cycle graph, path graph, hypercube graph and bipartite complite graph. The mirror graph of cycle graph, path graph, hypercube graph, and bipartite complite graph are E-cordial graphs.